(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Annotation: The article highlights the results of scientific research on the pathoanatomical and histological study of experimental rabbits infected with atypical mycobacteria. It has been established that the latter are able to cause rather deep pathological processes in their body. These processes are characterized, in addition to general hemodynamic disorders, by the development of necrotic foci of various sizes in the liver